Genetic evaluation of functional longevity in South African Holstein cattle using a proportional hazards model - Imbayarwo-Chikosi, Venancio Edward (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.